Electrochemically-driven mineralization of Reactive Blue 4 cotton dye: On the role of in situ generated oxidants - Nakamura, Karen Christine; Guimarães, Luciana Silva; Magdalena, Aroldo G. [UNESP]; Angelo, Antonio Carlos Dias [UNESP]; De Andrade, Adalgisa R. [UNESP]; Garcia-Segura, Sergi; Pipi, Angelo R.F. (Elsevier, 2019)
Brazil is the fifth biggest global manufacturer of textiles and the fourth in cotton textile exports. Textile effluents contain organic dyes that are highly recalcitrant and difficult to oxidize by conventional physico-chemical and biological treatments. Mid-sized textile factories require reliable water treatment technologies of small physical foot-print that do no produce solid wastes to treat their manufacturing effluents. Electrochemically-driven technologies emerge as feasible alternative technologies that overcome barriers in the management of these industrial effluents. This work studies the application of electrochemical advanced oxidation processes on the treatment of dye bath effluents containing cotton dye Reactive Blue 4. Electro-Fenton treatment attains complete color removal with an electrical energy per order (E EO ) of 7.4 kWh m −3 order −1 , which represents an order of magnitude lower operational expenditure than electrochemical oxidation (54.8 kWh m −3 order −1 ). Simultaneous irradiation with UVA light in photoelectron-Fenton systems did not show any effect on RB4 degradation kinetics. But UVA irradiation increased the mineralization achieved after treatment, which enhanced current efficiencies ca. 2-fold respect to electro-Fenton.
Keywords: Anodic oxidation; Electro-Fenton; Electrochemical advanced oxidation processes; Water treatment